+0  
 
0
267
2
avatar

csc(acos(u))

Guest May 25, 2017
 #1
avatar+7155 
+2

\(\csc(\arccos u ) \\~\\ =\frac{1}{\sin(\arccos u)} \\~\\ =\sqrt{ (\frac{1}{\sin(\arccos u)})^2 } \\~\\ =\sqrt{ \frac{1}{\sin^2(\arccos u)} } \\~\\\)

 

And... sin2θ = 1 - cos2θ

 

\(=\sqrt{ \frac{1}{1-\cos^2(\arccos u)} } \\~\\ =\sqrt{ \frac{1}{1-\cos(\arccos u)\cos(\arccos u)} } \\~\\ =\sqrt{ \frac{1}{1-uu} } \\~\\ =\frac{1}{\sqrt{1-u^2}} \\~\\\)

 

laugh

hectictar  May 25, 2017
 #2
avatar+92806 
+2

This is how I would do it.

 

let acos(u) = alpha  

Draw a right angled triangle and let alpha be an acute angle.

since  cos( alpha) = u/1

let  the adjacent side by u and the hypotenuse be 1

using pythagoras's theorem you get  

 \(\text{opposite side=}\sqrt{1-u^2}\)

 

\(cosec(\alpha)=\frac{hyp}{adj}=\frac{1}{\sqrt{1-u^2}}\)

 

but you do not know which quadrant alpha is in so

 

\(cosec(\alpha)=\pm\frac{1}{\sqrt{1-u^2}}\)

Melody  May 25, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.